The timing for initiating estrogen stimulation in artificial cycle for frozen-thawed embryo transfer can be flexible - Ying Ying; Yixuan Wu; Shuang Liu; Qing Huang; Haiying Liu (BMC, 2021)
Plain Language summary Despite the continuous efforts invested in exploring and optimizing therapeutic regimens to improve the success rate of frozen-thawed embryo transfer (FET), we found that there are little evidence to demonstrate whether the initiation time of estrogen stimulation is flexible in the proliferative endometrial phase during the artificial cycle for FET (AC-FET). Thus, we retrospectively reviewed the FET records from a large university-affiliated reproductive medicine center to explore whether the relatively late start of endometrial stimulation for FET influences the pregnancy outcome. Results provided evidences that initiating the estrogen stimulation on after days 2-5 of menses do not exert adverse effects on the ongoing pregnancy rates in AC-FETs. Therefore, FET can be scheduled in a flexible manner, according to the ovulatory and endometrial statuses and patient and/or clinic preference, without compromised clinical outcomes.